2011
DOI: 10.4007/annals.2011.173.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Weyl group multiple Dirichlet series, Eisenstein series and crystal bases

Abstract: We show that the Whittaker coefficients of Borel Eisenstein series on the metaplectic covers of GLr+1 can be described as multiple Dirichlet series in r complex variables, whose coefficients are computed by attaching a number-theoretic quantity (a product of Gauss sums) to each vertex in a crystal graph. These Gauss sums depend on "string data" previously introduced in work of Lusztig, Berenstein and Zelevinsky, and Littelmann. These data are the lengths of segments in a path from the given vertex to the verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
139
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(141 citation statements)
references
References 28 publications
(62 reference statements)
2
139
0
Order By: Relevance
“…The variety Z w is always nonsingular, and may be built up by successive fiberings by P 1 , which corresponds to the procedure in representation theory of reducing a computation on G to a series of SL 2 computations. And this is what was done (for the full Eisenstein series, that is, for the case where w = w 0 ) in Brubaker, Bump and Friedberg [3].…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The variety Z w is always nonsingular, and may be built up by successive fiberings by P 1 , which corresponds to the procedure in representation theory of reducing a computation on G to a series of SL 2 computations. And this is what was done (for the full Eisenstein series, that is, for the case where w = w 0 ) in Brubaker, Bump and Friedberg [3].…”
mentioning
confidence: 59%
“…See the survey article Bump [5] for discussion of this this phenomenon and its history. An analysis of the proof of one particular case, in Brubaker, Bump and Friedberg [3] shows the mechanism behind this phenomenon makes use of Bott-Samelson varieties. In this connection, we call attention to one particular point: that such a representation of the Whittaker coefficient of an Eisenstein series as a sum over a crystal requires a choice of a reduced word, by which we mean a decomposition of the long Weyl group element w 0 into a product of simple reflections of shortest possible length.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Though we have described the series (1) in terms of global objects (Eisenstein series), let us also mention that the p-power supported terms are known to match the p-adic Whittaker function attached to the spherical vector for the associated principal series representation used to construct the Eisenstein series. This follows from combining the work of McNamara [17] with that of Brubaker, Bump and Friedberg [2,6], or by combining [2,17] and an unfolding argument of Friedberg and McNamara [11]. The precise definition of the coefficients H in the "stable" case will be reviewed in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Brubaker, Bump and Friedberg [6] have given an explicit description of the Whittaker coefficients of Borel Eisenstein series on the n-fold metaplectic cover of GL r+1 . In particular, they showed that the first nondegenerate Whittaker coefficient is a Dirichlet series in r complex variables (a "multiple Dirichlet series") that is roughly of the form…”
Section: Introductionmentioning
confidence: 99%